Beyond NATO A New Security Architecture for Eastern Europe - O'Hanlon, Michael (The Marshall Papers, 2017)
In this new Brookings Marshall Paper, Michael O'Hanlon argues that now is the time for Western nations to negotiate a new security architecture for neutral countries in eastern Europe to stabilize the region and reduce the risks of war with Russia. He believes NATO expansion has gone far enough. The core concept of this new security architecture would be one of permanent neutrality. The countries in question collectively make a broken-up arc, from Europe's far north to its south: Finland and Sweden; Ukraine, Moldova, and Belarus; Georgia, Armenia, and Azerbaijan; and finally Cyprus plus Serbia, as well as possibly several other Balkan states. Discussion on the new framework should begin within NATO, followed by deliberation with the neutral countries themselves, and then formal negotiations with Russia.